Paleoenvironments of a regressive Devonian section from Parana Basin (Mato Grosso do Sul state) by integration of ichnologic, taphonomic and sedimentologic analyses - Sedorko, Daniel; Bosetti, Elvio Pinto; Ghilardi, Renato Pinani [UNESP]; Myszynski Junior, Lucinei Jose; Silva, Rafael Costa; Scheffler, Sandro Marcelo (Soc Brasileira Geologia, 2018)
Studies that integrate ichnologic, taphonomic and sedimentologic data result in more accurate paleoenvironmental inferences than isolated approaches. Most of paleontological studies regarding Devonian from Parana Basin were conducted in the southern part of the basin (Parana state), precluding taphonomic or ichnologic studies to the northern part, and even its macrofossils content is understudied. This study analyzes paleoecologic and depositional conditions represented by trace fossils, macrofossils and sedimentary facies in a regressive Devonian section from Parana Basin, Mato Grosso do Sul state, Brazil. Seven ichnofabrics (Macaronichnus, Psammichnites, Arenicolites-Skolithos, Cylindrichnus-Skolithos, Zoophycos, Rhizocorallium-Palaeophycus, and Chondrites ichnofabrics) and three taphofacies (T1: parautochthonous to allochthonous preservation; T2: Autochthonous preservation; and T3: time-averaged autochthonous to allochthonous association) were diagnosed. The studied sections are positioned in a highstand systems tract (HST) exhibiting dominance of sandy facies, and four sub-environments were defined: foreshore; shoreface; storm-dominated shoreface to transitional offshore; and offshore. The dominance of foreshore to shoreface settings in a HST corroborates a shallower context in relation to the southern part. However, similarities in the facies and ichnofacies stacking, as well in the macrofossil content suggest that the hypothetical division between two sub-basins (Apucarana and Alto Garcas Sub-basins) was not complete until early Emsian.
Keywords: Ichnofacies; Taphofacies; Tempestites; Devonian; Sub-Basins